Adaptation and Validation of the School Climate and School Identification Measure-Student Scale (SCASIM-St) in a Sample of Chilean Adolescents - Gálvez-Nieto, José Luis; Vera-Bachmann, Daniela; Trizano-Hermosilla, Ítalo; Polanco-Levican, Karina; Briceño-Olivera, Claudio (Frontiers in Psychology, 2020)
The school climate construct has been linked to a series of positive outcomes in adolescence; however, the few validated instruments in Spanish have a fragile theoretical base. Consequently, the aim of this study was to adapt and validate the dual school climate and school identification measure-student (SCASIM-St) scale in a sample of Chilean adolescents. First, a linguistic adaptation of the instrument was completed, followed by a cross-sectional study. 1,456 students of both sexes participated in the study (41.1% boys and 58.9% girls), with an average age of 15.76 years (SD = 1.42), representing 17 secondary schools in Chile. Three confirmatory factor models were contrasted; the one with the best fit supported the originally proposed structure. The evidence of external criterion validity, confirmed through the Authoritative School Climate Survey (ASCS), showed a significant positive relationship between the two measures. This study verified the psychometric quality for the SCASIM-St scale, allowing for its use in the Chilean context. This instrument provides a measurement tool with a solid theoretical base that can be used in the Chilean context.